Activity of D1/2 Receptor Expressing Neurons in the Nucleus Accumbens Regulates Running, Locomotion, and Food Intake - Zhu, Xianglong; Ottenheimer, David; DiLeone, Ralph J. (Frontiers in Behavioral Neuroscience, 2016)
While weight gain is clearly promoted by excessive energy intake and reduced expenditure, the underlying neural mechanisms of energy balance remain unclear. The NAc is one brain region that has received attention for its role in the regulation of energy balance; its D1 and D2 receptor containing neurons have distinct functions in regulating reward behavior and require further examination. The goal of the present study is to investigate how activation and inhibition of D1 and D2 neurons in the NAc influences behaviors related to energy intake and expenditure. Specific manipulation of D1 vs D2 neurons was done in both low expenditure and high expenditure (wheel running) conditions to assess behavioral effects in these different states. Direct control of neural activity was achieved using a DREADD (Designer Receptors Exclusively Activated by Designer Drugs) strategy. Activation of NAc D1 neurons increased food intake, wheel running and locomotor activity. In contrast, activation of D2 neurons in the NAc reduced running and locomotion while D2 neuron inhibition had opposite effects. These results highlight the importance of considering both intake and expenditure in the analysis of D1 and D2 neuronal manipulations. Moreover, the behavioral outcomes from D1 NAc neuronal manipulations depend upon the activity state of the animals (wheel running vs non-running). The data support and complement the hypothesis of specific NAc dopamine pathways facilitating energy expenditure and suggest a potential strategy for human weight control.